2014
DOI: 10.2134/jeq2013.11.0466
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the SWAT Model Special Section: Overview and Insights

Abstract: The Soil and Water Assessment Tool (SWAT) model has emerged as one of the most widely used water quality watershed-and river basin-scale models worldwide, applied extensively for a broad range of hydrologic and/or environmental problems. The international use of SWAT can be attributed to its flexibility in addressing water resource problems, extensive networking via dozens of training workshops and the several international conferences that have been held during the past decade, comprehensive online documentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
260
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 508 publications
(277 citation statements)
references
References 48 publications
(216 reference statements)
7
260
0
10
Order By: Relevance
“…This marked improvement in model performance compared to simulations under the default mode emphasizes the importance of model calibration. This outcome is also consistent with previous summaries of SWAT streamflow statistical results across multiple studies, which revealed that the majority of computed monthly (and daily) statistics satisfied suggested criteria for satisfactorily replicating corresponding observed streamflows [42,43] .…”
Section: Discussionsupporting
confidence: 89%
“…This marked improvement in model performance compared to simulations under the default mode emphasizes the importance of model calibration. This outcome is also consistent with previous summaries of SWAT streamflow statistical results across multiple studies, which revealed that the majority of computed monthly (and daily) statistics satisfied suggested criteria for satisfactorily replicating corresponding observed streamflows [42,43] .…”
Section: Discussionsupporting
confidence: 89%
“…Muitos desses modelos necessitam de uma quantidade grande de informaçÔes sobre parĂąmetros fĂ­sicos da bacia e dos solos, cujas informaçÔes podem ser construĂ­das com o auxĂ­lio de tĂ©cnicas de SIG. Dentre os inĂșmeros modelos existentes atualmente, um dos mais utilizados em todo o mundo Ă© o Soil and Water Assessment Tool (SWAT) (Bressiani et al, 2015;Arnold et al, 2012;Santos, 2015;Gassman et al, 2014;Pagliero et al, 2014;, Srinivasan et al, 2009.…”
Section: Introductionunclassified
“…The SWAT-modeled hydrological cycle is based on the water balance, as documented by Arnold et al (1998). SWAT has been widely tested and successfully used to explore the effects of climate and land use/management changes on watershed hydrology and water quality (Nyeko, 2015;Panagopoulos et al, 2011;Douglas-Mankin et al, 2010;Zhang et al, 2013;Bosch et al, 2010;Wu and Chen, 2013;Xu et al, 2012;Zhang et al, 2008Zhang et al, , 2011Qiu et al, 2012;Gassman et al, 2014). Detailed descriptions of the mechanisms and structure of the SWAT model can be found elsewhere (Neitsch et al, 2011;Arnold et al, 2012).…”
Section: Model Descriptionmentioning
confidence: 99%